2010
DOI: 10.1186/1472-6831-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic disparity in oral health among the poor: a cross sectional study of early adolescents in Kilwa district, Tanzania

Abstract: BackgroundThere is a lack of studies considering social disparity in oral health emanating from adolescents in low-income countries. This study aimed to assess socio-demographic disparities in clinical- and self reported oral health status and a number of oral health behaviors. The extent to which oral health related behaviors might account for socio-demographic disparities in oral health status was also examined.MethodsA cross-sectional study was conducted in Kilwa district in 2008. One thousand seven hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 34 publications
6
40
0
4
Order By: Relevance
“…Also, in a recent study conducted in Tanzania, Mashoto et al reported that 21.9% of school children never brushed their teeth and 32.9% met the standard criteria. [24] This is totally comparable to the results we obtain since only 4% of the people were irregular in their brushing habits. But a study in Denmark showed that very good habits have been inculcated since 68% of the people brushed at least twice daily and 11% dental flossing.…”
Section: Discussionsupporting
confidence: 81%
“…Also, in a recent study conducted in Tanzania, Mashoto et al reported that 21.9% of school children never brushed their teeth and 32.9% met the standard criteria. [24] This is totally comparable to the results we obtain since only 4% of the people were irregular in their brushing habits. But a study in Denmark showed that very good habits have been inculcated since 68% of the people brushed at least twice daily and 11% dental flossing.…”
Section: Discussionsupporting
confidence: 81%
“…After adjusting for gender, age and residential area there seem an ascending trend between health-related behaviors and economic status. Likewise, in Tanzania, utilizing tooth brush was less common among adolescents from lower economic status (52). Also in a Korean study there was significant correlation between regular tooth brushing habits and individual's income (48).…”
Section: Oral Hygiene (Oh) and Socio-economic Factorsmentioning
confidence: 99%
“…Among school age children (6-14 years old) 14.3% brush their teeth twice a day, 9.4% use floss daily and only 2.7% meet both criteria. In a recent study in Tanzania, Mashoto et al reported that 21.9% of their study population which were schoolchildren never brushed their teeth and only 32.9% met the standard criteria for tooth brushing (52). In their latest resolution, WHO urged all communities to develop and implement oral health promotion programs in school children as part of activities in health-promoting schools (53).…”
Section: Oral Hygiene (Oh) Status In Iranmentioning
confidence: 99%
“…The wealth asset index was assumed to have direct effects on dental attendance, 38 family sugar consumption, 38 anthropometric status, 39,40 family oral hygiene, 38 breastfeeding duration 41 and breastfeeding exclusivity. 42 Maternal education was assumed to have direct effects on dental attendance, 42 family sugar consumption, 38 marital status, anthropometric status, 43 family oral hygiene, 38 breastfeeding duration 42 and EBF.…”
Section: Directed Acyclic Graphs (Dags)mentioning
confidence: 99%